Psychological wellbeing early adult Korean pop fangirls - Fitri, Angelita Jayalaksana; Maulidayanti, Fitri Yuli; Akhmad, Sudaryat Nurdin (Indonesian Institute for Counseling, Education, and Therapy & Indonesian Counselor Association, 2021)
Mental health is a state of well-being in which individuals are aware of their abilities, can cope with the normal stresses of daily life, can work productively or productively, and are able to contribute to their community. Individuals at the age from 20 to 40 years are called early adulthood. In the last two decades, South Korean popular culture has grown rapidly and expanded globally. Its existence which is accepted by the public from various circles has resulted in a phenomenon Korean Wave, one of which is the phenomenon in Korean Wave Korean pop music products or Korean-pop (K-pop). This study uses the study of literature (literature review) with data collection of articles, journals and books. The results showed that there was mental health (psychological wellbeing) in early adulthood for fangirls K-pop.